RITUAL KATINGKA DALAM PERLADANGAN MASYARAKAT ETNIK MUNA DI DESA BAHUTARA KECAMATAN KONTUKOWUNA KABUPATEN MUNA - Aswan Aswan; La Ode Topo Jers (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2018)
This study aims to determine the process of carrying out the katingka ritual carried out by Muna ethnic farmers in Bahutara Village, Muna Regency and analyze the meaning contained in it. The theory used in this study is the theory of symbols from Victor Turner. Data collection is done through observation and in-depth interviews. The data obtained were analyzed descriptively qualitatively. The results showed that the process of carrying out katingka was carried out at the location of the garden which had just been cleaned and had not been planted. The katingka ritual is carried out to unite the souls between farmers, garden land, and supernatural beings (kodasano) so that farmers stay healthy and get abundant crops. The main objective of farmers is to hold a katingka ritual, namely: first, as a form of respect and permission to Kodasano that they process the forest or land to be used as a plantation location. Second, to protect their plants from pest disorders, such as pigs and other types of plant diseases. Third, as one form of immunization or immunity to diseases for land processors and prevention of diseases against plants. In the lives of ethnic Muna farmers in Bahutara Village, this ritual contains religious meaning and the meaning of social control. Keywords: ritual, katingka, cultivation, farmers, munanese